2019
DOI: 10.1177/1754337118823603
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of impact attenuation by football helmets using a modal impulse hammer

Abstract: Concussions and changes in neurophysiology due to sub-concussive blows are common in contact sports, motivating a need for improved safety systems. While there have been attempts to determine whether or not new helmet designs influence the incidence of concussion, the results to date have been inconclusive. Consequently, the goal of this study was to evaluate the ability of modern football helmets to mitigate linear impacts directed normal, as well as oblique, to the surface of the helmeted head using a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The greater average PAA per HAE for GS players may also be due to the lack of or minimal protective head gear worn by these athletes, while FB players wear helmets that reduce some of the rotational acceleration that would otherwise be experience by the head. 68…”
Section: Discussionmentioning
confidence: 99%
“…The greater average PAA per HAE for GS players may also be due to the lack of or minimal protective head gear worn by these athletes, while FB players wear helmets that reduce some of the rotational acceleration that would otherwise be experience by the head. 68…”
Section: Discussionmentioning
confidence: 99%
“…As covered in section 2, there is ongoing discussion around the acceleration magnitudes and time profiles that are associated with clinical diagnosis of concussion, which should be resolved before updating standards [95]. As such, metrics are often compared to in-field measures for actual sporting collisions and falls, and those collected with an un-helmeted headform [190,[226][227][228][229].…”
Section: Helmet Testingmentioning
confidence: 99%
“…It should be noted, however, that the traditional drop-tower systems and the more modern versions that utilize pneumatic rams employ similar output metrics, which have never been validated against closed-head trauma. In 2019, Cummiskey et al (98) reported a system that integrated a modal impulse hammer to record the input force with a Hybrid III Headform adapted to output the translational and angular accelerations. Quantifying both the inputs and outputs makes it possible to obtain a transfer function at each impact location that can be used to evaluate the effects of specific helmet design elements.…”
Section: Protective Technologymentioning
confidence: 99%
“…These data provide the first true design goals for helmets and other protective systems aimed at reducing the cumulative burden of HAEs. Current data on football (98) and lacrosse helmets (99) suggest that helmets can be designed to achieve the 50-g threshold for the 95th percentile head impact observed in high school and collegiate contact sports. It should be noted, however, that the ultimate validation of new helmet features will require the aforementioned MRI gold standard to quantify changes in brain structure, function, and chemistry.…”
Section: Protective Technologymentioning
confidence: 99%